Mejoramiento en las propiedades físicas y químicas del cemento portland tipo MS por adición del clinker tipo V, en la sustitución de escoria BFS de alto horno - Cortéz Rojas, Manuel Fernando (2006)
In the present work, an investigation was proposed that provided experimental information, which showed the performance of Portland Cement type MS produced with Clinker type V, as a replacement additive of BFS blast furnace slag, in gradual percentages. Through the use of the theoretical information and the steps for the elaboration of Portland cement type MS, based on international standards, such as the ASTM Standard; A comparison was made between the production cost of the same, using BFS blast furnace slag and on the other hand using Clinker type V. This, in order to handle the possibility that the company of "Cementos Pacasmayo SAA" produces its own additive for the elaboration of its Cementos Portland type MS. This research work was carried out, because the company, within about 3 years, will not produce Portland Cement type MS based on BFS Slag, but would be manufacturing the new additive for the total replacement of it, when it is finished in due time; such is the case that the purchase of Escoria BFS is currently being reduced to the steel company Sider Perú de Chimbote. In the different analyzes carried out, the results have been optimal and those required by the ASTM Standard, since the study of cost and production will benefit the company going forward